Collaborative teaching / Wan Nurhasyimah W. Mohd Apandi and Mohd Daud Abdul Rahim - W. Mohd Apandi, Wan Nurhasyimah W. Mohd Apandi; Abdul Rahim, Mohd Daud (Universiti Teknologi MARA, Perak, 2020)
Collaborative teaching methods is related with Pedagogy theory in academician achievement as team members (Armstrong (1977); cited in David Nunan (1992)). The definition of collaborative teaching approach is known as team teaching in classrooms practices, with a group of creative thinkers to brainstorm about ideas or other creative problems. This practice should be done continuously to be effective. However, there are some challenges that educator will face when practicing collaborative teaching in classroom. The challenges include clash of teaching hours, misconducting time management for students, percentage of rubric assessment, and confusion in terms of differing opinion from educators. Collaborative teaching also known as team teaching is an approach to educate students with two or more teachers in the classroom for a same subject (Robinson et al., 1995).